2013
DOI: 10.3390/min3010094
|View full text |Cite
|
Sign up to set email alerts
|

Three Compositional Varieties of Rare-Earth Element Ore: Eudialyte-Group Minerals from the Norra Kärr Alkaline Complex, Southern Sweden

Abstract: Agpaitic nepheline syenites at the Norra Kärr Alkaline Complex, southern Sweden, are rich in zirconium and rare-earth elements (REE), which are mainly accommodated in eudialyte-group minerals (EGM). Norra Kärr hosts three compositionally distinct groups of EGM, which are complex zirconosilicates. Analyses of EGM by electron beam energy-dispersive (SEM-EDS) and wavelength-dispersive (WDS-EMP) X-ray microanalysis are presented and compared, complemented by whole-rock analyses. The SEM-EDS and WDS-EMP methods pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 27 publications
3
26
0
3
Order By: Relevance
“…4), emplaced at 1489 ± 8 Ma (Sjöqvist et al, 2013). Norra Kärr is a body of deformed, agpaitic, peralkaline nepheline syenite, about 1300 × 400 m in size, which is rich in eudialyte-group minerals and other REE-bearing minerals such as catapleiite (Sjöqvist et al, 2013). It has an NI-43-101 compliant indicated resource of 41.6 million tonnes (Mt) at 0.57% TREO, and an inferred resource of 16.5 Mt.…”
Section: Mesoproterozoic Rift Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…4), emplaced at 1489 ± 8 Ma (Sjöqvist et al, 2013). Norra Kärr is a body of deformed, agpaitic, peralkaline nepheline syenite, about 1300 × 400 m in size, which is rich in eudialyte-group minerals and other REE-bearing minerals such as catapleiite (Sjöqvist et al, 2013). It has an NI-43-101 compliant indicated resource of 41.6 million tonnes (Mt) at 0.57% TREO, and an inferred resource of 16.5 Mt.…”
Section: Mesoproterozoic Rift Systemsmentioning
confidence: 98%
“…This A-type suite includes some small bodies of peralkaline syenite with elevated REE contents, most notably the Norra Kärr Alkaline Complex in southern Sweden (Fig. 4), emplaced at 1489 ± 8 Ma (Sjöqvist et al, 2013). Norra Kärr is a body of deformed, agpaitic, peralkaline nepheline syenite, about 1300 × 400 m in size, which is rich in eudialyte-group minerals and other REE-bearing minerals such as catapleiite (Sjöqvist et al, 2013).…”
Section: Mesoproterozoic Rift Systemsmentioning
confidence: 99%
“…Trin-butyl phosphate (TBP) and Cyanex 923 (Cy923) were chosen because they are the most frequently used neutral extractants for REE extraction from nitrate media. 12,13,15,36,[50][51][52][53] However, in the present study, these extractants were applied for extraction from chloride aqueous media and dissolved in the ILs. 23 The results showed that the extraction of REE from feed solutions of 7 g L À1 of REE and 2 mol L À1 of CaCl 2 with [C101][NO 3 ] and [A336][NO 3 ] was not affected by the presence of TBP in both ILs.…”
Section: Extraction Tests Using An Organic Phase Composed Of Mixturesmentioning
confidence: 97%
“…This composition was chosen to simulate a pregnant leach solution (PLS) obtained aer HCl leaching of a REE concentrate produced from the eudialyte deposit of the Norra Kärr in Sweden. 12,13 The aqueous feed solutions for the extraction tests were prepared by mixing the CaCl 2 stock solution and solution A to achieve a nal CaCl 2 concentration between 1 and 4 mol L À1 and a total metal concentration between 0.05-0.3 mol L À1 (7 and 40 g L À1 ). In some cases, ethylene glycol (between 10 and 50 v%) was also added.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
See 1 more Smart Citation